PELAKSANAAN ROYA FIDUSIA KENDARAAN BERMOTOR SEBAGAI JAMINAN HUTANG DI BANK MESTIKA DHARMA TBK CABANG PEKANBARU. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Fiduciary guarantee is a guarantee institution that can be used to bind collateral objects in theform of movable and immovable property, especially buildings that cannot be burdened with mortgages.Roya (elimination) is the elimination of debts guaranteed by the fiduciary, the release of rights to theFiduciary Guarantee by the Fiduciary Recipient or the destruction of objects that are objects of fiduciarycollateral. Based on this, the emergence of how the implementation of the motor vehicle fiduciary roya ascollateral is payable at the Pekanbaru Branch Mestika Dharma Tbk. The formulation of the problem in thisstudy is how the implementation of the motor vehicle fiduciary roya as collateral for debt at the PekanbaruBranch of Mestika Dharma Tbk and how the legal consequences if it is not carried out motorized fiduciaryroya as collateral for debt at the Pekanbaru Branch Mestika Dharma Tbk. The purpose of this study is First,to find out the implementation of the motor vehicle fiduciary roya as collateral for debt at the PekanbaruBranch Mestika Dharma Tbk. Secondly, to find out the legal consequences if the motor vehicle's fiduciaryroya is not carried out as collateral for debt at the Pekanbaru Branch Mestika Dharma Tbk.The type of research I use is a type of sociological research. The research location that is the objectof this research is the Pekanbaru Branch Mestika Dharma Tbk, Notary and Kemenkumham Riau ProvinceRegional Office. While the population and samples use the Pekanbaru Branch Mestika Dharma Tbk Debtor,Bank Mestika Dharma Branch Head, Notary and Kemenkumham Riau Province Regional Office. Primary,secondary and tertiary data sources. Data collection techniques in this study were interviews,questionnaires and literature review.From the results of the study there are several problems that give rise to two points. First, thequestion is how the implementation of the fiduciary law and legal consequences if it is not carried out by thefiduciary roya of motorized vehicles as collateral for debts at the Pekanbaru Branch Mestika Dharma Tbk,namely not all carry out the fiduciary plan because even if no deletion is carried out. . Second, how theefforts made to carry out motor vehicle fiduciary operations as collateral for debt at the Pekanbaru BranchMestika Dharma Tbk, namely when the debtor will pledge the object or item back then the object or itemcannot be guaranteed back for fiduciary collateral, because in fiduciary guarantee it does not allowfiduciary re. Suggestion of the author, first, even though there is no strict sanction, it should still carry outthe elimination of fiduciary. Second, the author hopes that there will be an effort from the government tomake more stringent rules regarding the provisions for the abolition of fiduciary guarantees.Keywords: Implementation - Roya - Fidusia - Vehicles - Motorized